Macrophage Receptor With Collagenous Structure Polymorphism and Recurrent Respiratory Infections and Wheezing During Infancy: A 5-Years Follow-Up Study - Savino, Francesco; Pellegrino, Francesco; Daprà, Valentina; Calvi, Cristina; Alliaudi, Carla; Montanari, Paola; Galliano, Ilaria; Bergallo, Massimiliano (Frontiers in Pediatrics, 2021)
Background: Recurrent wheezing is a common clinical manifestation in childhood and respiratory syncytial virus infection is a well-known risk factor. However the genetic background favoring the development of recurrent wheezing is not fully understood. A possible role of macrophage receptor with collagenous gene (MARCO) polymorphism has been recently proposed. Objective: To investigate a correlation between MARCO rs1318645 polymorphisms and susceptibility to recurrent wheezing during childhood. Methods: We prospectively recruited 116 infants, of which 58 with respiratory syncytial virus bronchiolitis and 58 controls hospitalized at Regina Margherita Children’s Hospital, Turin Italy between November 2014 and April 2015. All subjects were investigated for MARCO rs1318645 polymorphisms in the first period of life by Genotyping of rs1318645 was carried out by TAQMAMA real-time polymerase chain reaction procedure. Subjects were then enrolled in a 5 year follow up study to monitor occurrence of wheezing and respiratory infections. Results: The analysis of MARCO rs1318645 of allelic frequencies shows an increased significant risk to develop recurrent infection (p value= 0.00065) and recurrent wheezing (p value= 0.000084) with a wild-type C allele compared to a G allele. No correlation was found between wheezing and past RSV infection (p value = 0.057) and for history of atopy in the family (p-value= 0.859). Conclusion: Our finding showed that subjects with C allelic MARCO rs1318645 polymorphism are at higher risk for recurrent infection and wheezing episodes during the first 5 years of life. Future studies of genetic associations should also consider other types of polymorphisms.